2010
DOI: 10.1007/s12010-010-9036-7
|View full text |Cite
|
Sign up to set email alerts
|

Galanthamine and Related Alkaloids Production by Leucojum aestivum L. Shoot Culture using a Temporary Immersion Technology

Abstract: The process of galanthamine and related alkaloids production by Leucojum aestivum shoot culture in a temporary immersion system was studied. It was established that temporary immersion approach is prospective for development of a biosynthetic process for obtaining valuable Amaryllidaceae alkaloids. Both immersion frequency and temperature had significant effect on biomass accumulation and the yields of galanthamine and related alkaloids. The maximal yield of galanthamine was achieved at the cultivation of L. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 32 publications
4
61
0
Order By: Relevance
“…Somatic embryogenesis can greatly improve the multiplication rate of in vitro bulbous plants. In the future, plants could be regenerated from somatic embryos and propagated in bioreactors, as previously shown for shoot cultures [14,15]. Therefore, the capacity of Leucojum aestivum embryogenic callus and the impact of both phenolic compounds and Amaryllidaceae alkaloids on the biosynthetic pathway were estimated for the first time under the influence of various auxins (2,4-D, picloram, and dicamba).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Somatic embryogenesis can greatly improve the multiplication rate of in vitro bulbous plants. In the future, plants could be regenerated from somatic embryos and propagated in bioreactors, as previously shown for shoot cultures [14,15]. Therefore, the capacity of Leucojum aestivum embryogenic callus and the impact of both phenolic compounds and Amaryllidaceae alkaloids on the biosynthetic pathway were estimated for the first time under the influence of various auxins (2,4-D, picloram, and dicamba).…”
Section: Introductionmentioning
confidence: 97%
“…The low Amaryllidaceae alkaloid accumulation commonly observed in in vitro cultures of Leucojum aestivum [6,[9][10][11][12][13] was probably due to the fact that the level of the alkaloid biosynthesis is strongly influenced by cellular differentiation [10,[14][15][16]. In particular, enhanced synthesis of galanthamine accompanied development of somatic embryos [17].…”
Section: Introductionmentioning
confidence: 99%
“…These cultivation systems were developed mainly for the needs of plants micropropagation (Debnath 2009) but, recently, they found application in transgenic plant regeneration (Hanhineva and Karenlampi 2007) and secondary metabolite production (Pavlov and Bley 2006;Ivanov et al 2011). Their suitable design allowed an effective separation of the resin nets from the explants.…”
Section: Resultsmentioning
confidence: 99%
“…The temporary immersion system was reported for micropropagation of Leucojum aestivum somatic embryo and shoot cultures [12,27]. It was also observed that liquid medium affected an increase in the number and FW of bulbs, for example in tulip culture [20], while temporary immersion systems stimulated tuberization of potato [26].…”
Section: Disscusionmentioning
confidence: 94%